(untitled) (Research, Society and Development, 2021)
Analyzing memes and verbal and non-verbal language in the day-to-day of Portuguese language classes represents building some reflections for the appreciation and scope of the discursive materialities of memes within the school context. With the advent of the digital age, a lot of content is spread all the time, including memes. Therefore, several hypotheses arise and, among them, whether the verbal and non-verbal language within Portuguese language classes, through the analysis of memes, would promote learning in the Basic School. In view of the proposition, the fundamental objective of the study was outlined, which is to analyze the Languages ​​axis and its codes through the appreciation of memes in the context of the day-to-day context of Portuguese language classes. It is intended, in an analytical case study, to read and select some texts, following the criteria: actuality, original and intelligent graphic proposal, social service and creatively approached. The corpora will be technologically disseminated texts for the description and explanation for a more active work in the school that at the moment lacks support for new proposals coming from paths beyond books and handouts. The basic theorists will be: Bronckart (2005); Kleiman (2007); Xavier (2002); Soares (2004) and BNCC (2016), among other authors. It is believed that verbal and non-verbal language within the context of daily life in Portuguese language classes can lead students to the perception of different semiosis proposed by the languages made possible by technology/WEB.